EVALUASI PENERAPAN SISTEM INFORMASI MANAJEMEN KEUANGAN DAERAH (SIMDA) PADA BIRO KEUANGAN SEKRETARIAT DAERAH PROVINSI KALIMANTAN TIMUR - Suwindra Yudha Pratama (Magister Administrasi Publik FISIP Universitas Mulawarman, 2017)
This study aims to evaluate the application of SIMDA (regional of financial management information system) at the local finance bureau secretariat east Kalimantan province, and to know the constraints and efforts in the implementation of SIMDA. The results showed that, evaluation of the application SIMDA at the local finance bureau secretariat east Kalimantan province have been going well this can be seen from the results achieved after application, because it can be more quickly, accurately and timely. Financial SIMDA also help facilitate the process of preparation of financial statements, employee living record / input data on the system, although there are still some obstacles still to be faced in terms of human resources, infrastructure and technology.